GENETIC VARIABILITY STUDIES IN F2 GENERATION OF TION OF PUMPKIN ( PUMPKIN (CUCURBITA MOSCHATA DUCH EX. POIR) - V. KRISHNAMOORTHY,; T. V. AVINASHGUPTA, (The Bioscan, 2019)
The present investigation was carried out to determine the variability, heritability and genetic advance in F2 generation of pumpkin during kharif, 2017. A wide variability was observed for most of the traits like vine length 2.7 to 7.38 m, sex ratio 14.22 to 20.16, average fruit weight 1.24 to 3.58 kg, fruit length 12.3 to 16.89 cm, fruit diameter 46.41 to 57.42 cm, number of seeds per fruit 274.5 to 397.10 and fruit yield per plant 2.15 to 6.52 kg. High PCV and GCV was observed in crosses P6XP5 for vine length (23.74, 21.73), days to first female flowering (4.74, 2.26), yield per plant (81.58, 75.74), P5XP3 for sex ratio (16.21, 9.10), number of fruits (34.68, 21.51), P2XP6 for days to first harvest (1.23, 1.60) and fruit weight (40.40, 39.57). High heritability was recorded in the cross P3XP5 for days to male flowering (65.80), days to first female flowering (65.80), sex ratio (76.25), average fruit weight (96.07) and fruit yield (58.66) with high genetic advance. The high heritability coupled with high genetic advance for fruit yield and fruit weight was recorded in the cross P3XP5 (58.66, 71.64).